Nutrition for health, fitness, & sport - Williams, Melvin H. (McGraw-Hill, 2012)
This textbook provides the reader with thorough coverage of the role nutrition plays in enhancing one's health, fitness and sport performance. Current research and practical activities are incorporated throughout.